Projeto de prevenção primária e secundária de doenças cardiovasculares da FCT/UNESP de Presidente Prudente - Torquato, Paula Rapchan dos Santos [UNESP]; Oliveira, Elaine Aparecida de [UNESP]; Silva, Vitor Eduardo dos Santos [UNESP]; Alves, Rafaella de Sá Turini [UNESP]; Santos, Gisele Carla Gonçalves dos [UNESP]; Haddad, Maria Isabela Ramos [UNESP]; Vanzella, Laís Manata [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: The cardiovascular disease have a significant increase along the years, increasing the number of deaths related with thispatology. Your appearance is relate with a number of risk factors that direct the prevention programs, searching the health benefits of the participants. Objective: Describe the activity developed on the Primary and Second Cardiovascular Disease Prevention Project of Attendance and Studies Center in Physical Therapy and Rehabilitation (FCT/UNESP) and characterize the individuals participants of this project on 2015. Materials and methods: The project is develop with patients of Attendance and Studies Center in Physical Therapy and Rehabilitation (FCT/UNESP/PresidentePrudente) doing preventive cardiovascular risk factors activities like obesity, blood pressure, diabetes, dyslipidemia, sedentarism, smoking and stress. These activities involving questionnaires application, preventive activities, and evaluation. To characterize the sample we utilized descriptive statistical. Results and Discussion: There is on the project participants higher prevalence of seniors, individuals classified as overweight with the BMI, and moderate to high risk on waist-to-rip ratio. The project development have been promoting benefits effects on the life style of the participant population, and, contributing professionally and personally to the project integrant studies. Conclusion: The primary and secondary prevention program have fundamental importance, addressing the cardiovascular disease risk factors, and how to modify then, and contributes with de integral formation of the project participants studies.

Introdução: As doenças cardiovasculares têm aumentado significativamente com o passar dos anos, aumentando o numero de mortes relacionada a esta. Seu aparecimento se relaciona a diversos fatores de risco que direcionam a atuação de projetos preventivos, em busca de benefícios à saúde dos participantes. Objetivo: descrever as atividades desenvolvidas no Projeto de prevenção primária e secundária de doenças cardiovasculares no Centro de Estudos e Atendimento em Fisioterapia e Reabilitação da FCT/UNESP e realizar uma caracterização dos indivíduos que participaram no ano de 2015 desse projeto. Materiais e métodos: O projeto é desenvolvido com indivíduos frequentadores do Centro de Estudo e Atendimento em Fisioterapia e Reabilitação da FCT/UNESP/Presidente Prudente por meio da realização de atividades preventivas com fatores de risco cardiovasculares como obesidade, hipertensão arterial, diabetes, dislipidemia, sedentarismo, tabagismo e estresse. Estas atividades englobam a aplicação de questionários, atividades preventivas, e avaliações. Para a caracterização da amostra foi utilizada estatística descritiva. Resultados e discussão: Nos indivíduos que participaram do projeto, encontra-se maior prevalência de idosos, indivíduos classificados com sobrepeso por meio do IMC, e risco moderado à alto de acordo com a relação cintura/quadril. O desenvolvimento do projeto vêm promovendo efeitos benéficos no estilo de vida da população participante e contribuindo do ponto de vista profissional e pessoal com os alunos integrantes do projeto. Conclusão: O programa de prevenção primária e secundária tem fundamental importância abordando os fatores de risco de doenças cardiovasculares e como modificá-los, além de contribuir com a formação integral do alunos participantes do projeto.
Keywords: Risk factor; Prevention; Cardiovascular disease; Fatores de risco; Prevenção; Doenças cardiovasculares